2018
DOI: 10.1016/j.jssr.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing minority: Images of ethnic minority groups in Chinese elementary social studies textbooks

Abstract: This study investigates the visual representation of ethnic minority groups in Chinese elementary social studies textbooks. The author conducts a content analysis to examine the extent to which ethnic minority groups are visually represented and to explore the ways in which they are portrayed in some of the most popular social studies textbooks in China. A total of 6075 visuals drawn from 36 books were electronically coded and analyzed using SPSS. The findings reveal the dearth of ethnic minority-related visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Students as in secondary schools are often bound to learn from and accept information presented in textbooks which are shaped by their authors' positions and expectations about the target audience (Apple, 2004). Textbooks also comprise hidden curriculum (Chu, 2018) that is not openly taught but learned by students through transfers of dominant power structures and cultural norms immersed in the texts (Eisner, 2002). Therefore, textbooks can be used to shape identities and mobilize citizens (Chu, 2018), such as English.…”
Section: Introductionmentioning
confidence: 99%
“…Students as in secondary schools are often bound to learn from and accept information presented in textbooks which are shaped by their authors' positions and expectations about the target audience (Apple, 2004). Textbooks also comprise hidden curriculum (Chu, 2018) that is not openly taught but learned by students through transfers of dominant power structures and cultural norms immersed in the texts (Eisner, 2002). Therefore, textbooks can be used to shape identities and mobilize citizens (Chu, 2018), such as English.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has revealed that images aiming to represent an ethnic minority group usually consist of more women than men, such as in Chinese history textbooks and in films that adapt ethnic minority folktales or use ethnic minority people as main characters (Harrell, 1995;Chu, 2018). This gender imbalance makes it worthwhile to look at the issue from a feminist perspective.…”
Section: Introductionmentioning
confidence: 99%
“…I choose to investigate the medium of comics -firstly, as a Chinese female graphic art practitioner and a comic reader myself, I am familiar with the way sequential graphic narratives work and have background knowledge of the contemporary Chinese comic art market. Additionally, the comic book medium has been overlooked in earlier research of ethnic minority images (Chu, 2018;Gladney, 1995;Yang, 2011;Zhang, 1997), and my study is intended to contribute to this gap. Lastly, comic art on the representation of ethnic minority people is rare and worth investigating.…”
Section: Introductionmentioning
confidence: 99%
“…Textbooks are still common teaching materials used by teachers in the learning process (Chu, 2018). The use of printed textbooks (56.5%) is more common than the digital version (Hales, 2016).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The low understanding of students' concepts can be caused by the learning process given cannot connect material concepts with everyday life (Wicaksono et al,2017). The use of printed books, in general, is still not able to train students' ability to understand concepts optimally (Chu, 2018). This is because textbooks, in general, are still dominated by verbal explanations or words and lack of images that can visualize processes related to the concept of Biology.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%